Scrabble Game: Boosting Vocabulary Mastery of English Foreign Language (EFL) Students - Tuti Tuti; Ilinawati Ilinawati (Journal of English Education and Teaching, 2022)
The background of this research is the lack of student participation and involvement in learning English in the classroom especially for vocabulary learning. This is caused by the lack of students’ motivation, laziness and less understanding of students in mastering vocabulary. The purpose of this research is to describe the students’ participation and the students’ improvement in vocabulary after applying scrabble games. The method used in this research was Classroom Action Research (CAR). The data collection technique of this research are observation, interview, and measurement. The tools of data collection technique are observation sheet, interview guideline, and test. The researchers applied Classroom Action Research (CAR) where the data divided into two kinds of descriptions; they were Qualitative and quantitative. The researchers obtained the data from cycle one and cycle two and then described it into qualitative and quantitative description. From data the analysis, it showed that there was a significant improvement in the students' participation and students vocabulary mastery. It can be seen from qualitative and quantitative data. From qualitative data, the students’ participations were increased from the first cycle into two cycle. Meanwhile, from quantitative data, the result of the test improved significantly from both cycles.  It could be concluded that the scrabble game technique improved students’ vocabulary mastery.